The Role of Rhetoric and Intonation in the Ansprache zum Welt-Frauentag by Federal President Frank-Walter Steinmeier - Firli Mar’atus Sholikah; Agus Ridwan (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
This study was motivated by the phenomenon of increasing anti-feminism and digital misogyny in Germany, where constitutionally guaranteed equality has suffered a practical setback in the form of a decline in female representation in the Bundestag to 32,4%. This situation has triggered an urgent need for persuasive communication through state addresses. This study aims to analyze the emotional rhetoric (pathos) and intonation strategies in the Ansprache zum Welt-Frauentag in order to raise audience awareness. The method used is a mixed method of qualitative analysis of rhetoric by Aristoteles (2007) and quantitative digital acoustic analysis using Praat software supported theory by Kohler (1995). The data for this analysis are transcripts and audio recordings of the Ansprache zum Welt-Frauentag delivered by Bundespräsident Steinmeier. The results of the study identified three typologies of relationships between diction and intonation, namely contradiction, in which emotional diction is delivered in a flat tone to maintain objectivity; compensation, in which neutral legal references are given emotional weight through a rise in tone (late peak); and parallelism, which is the harmony between emotional diction and the highest voice frequency to build strong authority. Thus, this study confirms that the effectiveness of persuasion in a speech does not only depend on the text, but also on the flexibility of manipulating voice frequency, which strategically functions as an instrument for navigating the audience’s emotions.